Revision of the Afrotropical species of Asura Walker, 1854 (Lepidoptera: Arctiidae, Lithosiinae), with the description of a new genus - Durante, Antonio (Zootaxa, 2009)
The Afrotropical species of Asura Walker, 1854 are revised, and Afrasura, gen. n., is proposed to accommodate the group. The new genus is differentiated from Asura Walker, 1854 by external features and the morphology of the genitalia. Twenty-one new combinations and/or new species are proposed: Afrasura indecisa (Walker, 1869) comb. n., status rev. (type species); Afrasura amaniensis (Cieslak & Häuser, 2006) comb. n.; Afrasura crenulata (Bethune-Baker, 1911) comb. n., stat. rev; Afrasura discocellularis (Strand, 1912) comb. n., stat. rev.; Afrasura discreta sp. n.; Afrasura dubitabilis sp. n.; Afrasura emma sp. n.; Afrasura hieroglyphica (Bethune-Baker, 1911) comb. n., stat. rev.; Afrasura hyporhoda (Hampson, 1900) comb. n.; Afrasura ichorina (Butler, 1877) comb. n.; Afrasura neavi (Hampson, 1914) comb. n., stat. rev.; Afrasura numida (Holland, 1893) comb. n.; Afrasura obliterata (Walker, 1864) comb. n.; Afrasura pallescens sp. n.; Afrasura peripherica hilara (Kiriakoff, 1958) comb. n.; Afrasura rivulosa (Walker, 1854) comb. n.; Afrasura submarmorata (Kiriakoff, 1958) comb. n.; Afrasura terlineata sp. n.; Afrasura violacea (Cieslak & Häuser, 2006) comb. n.; and two unplaced species. The following subspecies are proposed: Afrasura indecisa orientalis ssp. n.; Afrasura rivulosa ethiopica ssp. n. The following names are synonymized: Asura fulvia Hampson, 1900 syn. n. and Asura obsolescens Hampson, 1914 syn. n., both synonyms of Afrasura rivulosa (Walker, 1854) comb. n.; Asura xantha Bethune-Baker, 1911 syn n., synonym of Afrasura indecisa (Walker, 1869) comb. n., stat. rev. A checklist and key to the species of Afrasura gen. n. are provided; habitus and genitalia of all taxa are figured.